Hubungan Sosial Ekonomi Dan Tatus Gizi Dengan Kejadian Menarche Dini pada Anak Sekolah Siswi Kelas V dan VI di SDN 205 Kota Baru Kota Jambi - Hasyim Kadri (Jurnal Ilmiah Universitas Batanghari Jambi, 2018)
Menarche is the beginning of menstruation in a girl at puberty, which usually appears at the age of 11-14 years. Menarche is a sign of a social status change from child to adolescent, adolescent girls who have a neurotic tendency in the age of puberty experience many mental conflicts with the arrival of the first menstruation that can lead to pathological behavior (Sukarni k, et al 2013), the occurrence of Menarche at each Women are not the same because there are several factors that influence it, including socio-economic factors, heredity, social environment and also health factors and nutritional status. Teenagers who are obese usually tend to experience Menarche earlier than thin young women (Andira, D. 2010). Data obtained in SDN 205 City Jambi amounted to 45 respondents. Research Objectives Knowledge of Social Environment Relationship, Socioeconomic Status, Nutrition Status and Media Period simultaneously with the incidence of Early Menarche In schoolchildren grade V and VI SDN 205 City District Baru City Jambi. The design of this research is qualitative with analytical survey research method, using Cross Sectional approach. Population in this research is all student of class V and VI which Menarche early at SDN 205 City Jambi. The sample in this study is the total (Total Sampling) of grade V and VI students who have Menarche in SDN 205 City Jambi which amounted to 45 Respondents. In this investigation, Univariate, Bivariate and Multivariate analyzes were conducted. The result of the analysis shows that there are social environment relation (p value 0.000), economic social (p value 0.000), nutritional status (p value 0.000) and mass media (p value 0.002). It is suggested to increase the counseling of Menarche early and Menarche pain to students and also to activate UKS activities.